Gastric emptying in rats with gastroduodenal disease induced by N-methyl-N-nitro-N-nitrosoguanidine and alcohol - Pokorn, Dražigost (Radiology and oncology (Ljubljana), 1996)
The rate of gastric emptying was measured with a dye dilution technique in rats treated with N-methyl-N-nitro-N-nitrosoguanidine and alcohol. Gastric emptying was compared in rats with gastroduodenal inflamatory diseases and gastroduodenal neoplasms, and in those without gastroduodenal disease. Gasttric emptying was found to be significantly increased following the intragastric injection of liquid meal in rats with gastroduodenal diseases as opposed to the control group of healthy rats. These findings suggest than an increased gastric emptying of liquids can be explained by abolition on the relaxation of the gastric wall in rats with gastroduodenal diseases.
Keywords: fiziologija; medicina; podgane; prebavila; želodčne bolezni; želodec